2013
DOI: 10.3171/2013.6.jns122403
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cerebral spinal fluid drainage associated with complications in patients admitted with subarachnoid hemorrhage

Abstract: Object Cerebral artery vasospasm is a major cause of death and disability in patients recovering from subarachnoid hemorrhage (SAH). Although the exact cause of vasospasm is unknown, one body of research suggests that clearing blood products by CSF drainage is associated with a lower frequency and severity of vasospasm. There are multiple approaches to facilitating CSF drainage, but there is inadequate evidence to determine the best practice. The purpose of this study was to explore whether continuous or inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…While this study is the first prospective study designed to monitor the primary outcome of EVD occlusion, the results are, for the most part, consistent with published literature from retrospective series. The incidence of occlusion documented in this study falls within the range of previous studies that suggested nonpatent EVD in 19% to 47% of patients; 3,4,15 however, the need for replacement is much higher than in previous retrospective studies, which have suggested a rate of 1% to 7%. [1][2][3]5,8,9,20 The reasons for higher permanent occlusion documented in the present study are likely multifactorial, but could be related to more rigorous prospective monitoring and reporting of occlusion in this study in comparison with retrospective studies, which likely failed to identify a subset of occlusions due to inadequate documentation, and/or a high-volume academic neurosurgical patient population with a large proportion of subarachnoid hemorrhage and otherwise complex patients, which may be a higher risk patient population for occlusion.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…While this study is the first prospective study designed to monitor the primary outcome of EVD occlusion, the results are, for the most part, consistent with published literature from retrospective series. The incidence of occlusion documented in this study falls within the range of previous studies that suggested nonpatent EVD in 19% to 47% of patients; 3,4,15 however, the need for replacement is much higher than in previous retrospective studies, which have suggested a rate of 1% to 7%. [1][2][3]5,8,9,20 The reasons for higher permanent occlusion documented in the present study are likely multifactorial, but could be related to more rigorous prospective monitoring and reporting of occlusion in this study in comparison with retrospective studies, which likely failed to identify a subset of occlusions due to inadequate documentation, and/or a high-volume academic neurosurgical patient population with a large proportion of subarachnoid hemorrhage and otherwise complex patients, which may be a higher risk patient population for occlusion.…”
Section: Discussionsupporting
confidence: 40%
“…Olson et al, in a randomized study comparing continuous versus intermittent drainage, showed a significantly lower occlusion rate with intermittent drainage than continuous drainage. 15 However, occlusion was poorly defined in this study and was not the primary outcome of this trial. The present study suggests that strategies for improving procedures that increase the incidence of ideal catheter position, as well as the preferential selection of larger diameter catheters, may potentially reduce the incidence of occlusion and need for replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous drainage has been shown to be associated with worse adverse events in aSAH 57 "High-dose barbiturate administration is recommended to control elevated ICP refractory to maximum standard medical and surgical treatment"…”
Section: Hyperosmolar Agentsmentioning
confidence: 99%
“…The investigators found that the overall rate of complications (EVD blockage, infection, CSF leak, hemorrhage) was higher in the continuous drainage group, but there were no significant differences in ICP control, rates of delayed cerebral ischemia (DCI), or functional outcomes. 57 The optimal duration of CSF diversion, and the techniques for EVD weaning, were not explored in this study and remain the target of future investigation.…”
mentioning
confidence: 99%